2021
DOI: 10.3389/fpsyg.2021.765180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Instigated Changes on Loneliness of Teachers and Motivation–Engagement of Students: A Psychological Analysis of Education Sector

Abstract: Upon the spread of the global pandemic of COVID-19, education was transformed online in an abrupt manner. Amid this change, the education sector did not have room for proper decision-making and understanding of psychological effects. This theoretical analysis aims to contribute to the proposed Frontiers Research Topic, through (a) in-depth analysis of the pandemic status and behavioral psychology and (b) examining educational psychology from the perspective of teachers regarding sudden changes. As a result, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…The study variable methodology and teaching support received the highest average scores, where the high assessment of the students about the proposed model stands out in the context of the COVID-19 pandemic, where the exhaustion and commitment of the students were strongly supported by teachers (Telyani et al, 2021). On this point, the authors Daumiller et al (2021) point out that the transition from face-to-face teaching to online teaching necessarily requires teachers to design high-quality teaching material, should know how to virtually communicate content to their students, and how to improve teacher-student and student-teacher interaction (Revilla-Cuesta et al, 2021).…”
Section: Methodology and Teacher Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…The study variable methodology and teaching support received the highest average scores, where the high assessment of the students about the proposed model stands out in the context of the COVID-19 pandemic, where the exhaustion and commitment of the students were strongly supported by teachers (Telyani et al, 2021). On this point, the authors Daumiller et al (2021) point out that the transition from face-to-face teaching to online teaching necessarily requires teachers to design high-quality teaching material, should know how to virtually communicate content to their students, and how to improve teacher-student and student-teacher interaction (Revilla-Cuesta et al, 2021).…”
Section: Methodology and Teacher Supportmentioning
confidence: 99%
“…For example, researchers Daumiller et al (2021) in a study on attitudes, exhaustion, and cognitive commitment among teachers and students showed that the teaching and learning approaches in the online transition were positive. In addition, other studies showed that in times of pandemic situations, communication has been ineffective in student-teacher and teacher-student interaction, which translates into challenges for effective learning (Telyani et al, 2021).…”
Section: Effects Of Covid-19 On Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: built by the authors based on (Kegan, 1982;Kozlovska et al, 2021;Telyani et al, 2021) At the third -interpersonal -stage, students are motivated by the desire to increase their authority among fellow members, and they also feel the need for recognition. The teacher at this stage can help to strengthen the management and increase the student's self-esteem.…”
Section: Figure 1 the Role Of The Teacher's Personality In Motivating...mentioning
confidence: 99%
“…Practical knowledge of a foreign language is an indisputable advantage of any specialist (Tkachenko et al, 2021;Turski et al, 2021). However, students do not consider it necessary to study, believing that they will not need a foreign language in their professional activities (Muradov et al, 2020;Riyanti, 2020;Telyani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%